Estuary 2018
DOI: 10.5772/intechopen.71808
|View full text |Cite
|
Sign up to set email alerts
|

Weather, Hydrological and Oceanographic Conditions of the Northern Coast of the Río de la Plata Estuary during ENSO 2009–2010

Abstract: Climatic, hydrological, and oceanographic conditions were determined during the 2009-2010 El Nino/Southern Oscillation (ENSO) on the north coast of the Río de la Plata (RdlP) estuary. The maximum monthly rainfall was observed in the middle and upper La Plata basin during September 2009 and February 2010 ("El Niño" phase, (EN)). The monthly flow of RdlP showed an increase with rainfall and significant differences between ENSO phases. The wind stress showed fluctuations in both phases, being less intense during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
0
8
0
3
Order By: Relevance
“…For the RdlP estuary, the historical environmental and hydrological data ranged from 1981 to 1999 (e.g., [ 37 ]), and for hydrology, plankton and fisheries from the 2000s to the present [ 46 , 47 ]. In addition, recent climatic, environmental and hydrological data were included (e.g., [ 38 , 39 , 40 , 48 ]).…”
Section: Research Methods: Approach and Estuaries Descriptionsmentioning
confidence: 99%
“…For the RdlP estuary, the historical environmental and hydrological data ranged from 1981 to 1999 (e.g., [ 37 ]), and for hydrology, plankton and fisheries from the 2000s to the present [ 46 , 47 ]. In addition, recent climatic, environmental and hydrological data were included (e.g., [ 38 , 39 , 40 , 48 ]).…”
Section: Research Methods: Approach and Estuaries Descriptionsmentioning
confidence: 99%
“…The fifth IPCC report (AR-5) on adaptation in CSA showed that SLR increased from 2 mm/yr in 1950 to 7 mm/yr in 2008 threatening corals, fish stocks and mangroves (Magrin et al, 2014). ENSO-related variability has been associated with ecological changes in the coastal environment in CSA (Brugnoli et al, 2018;IPCC, 2014d;Wong et al, 2014), while extreme weather events have affected people, including fatalities, displacement and economic losses .…”
Section: Climate Threats and Impacts On Coastal Areas Of Latin Americamentioning
confidence: 99%
“…Esta especie se encuentra adaptada a condiciones variables (salinidad, turbidez, temperatura) del área de estudio correspondientes a la zona del frente de turbidez (Derisio et al, 2014). Durante El Niño (2009-2010) se reportan elevadas descargas del Río Uruguay y Río Paraná y un incremento en el estado trófico (Brugnoli et al, 2018;. Durante esta fase, el aumento de caudal promovió un incremento en la abundancia y riqueza de cladóceros de agua dulce, originando una heterogeneidad espacial (abundancia y riqueza) del mesozooplancton en la ZCM.…”
Section: Variación Ambiental Y Mesozooplanctonunclassified
“…En el RdlP, el evento ENOS es una forzante atmosférica a gran escala, ocasionando efectos en las descargas de los ríos, modificaciones en la dinámica físico-química, en la ubicación de los frentes de turbidez o salinidad, en la dinámica de los nutrientes y en el estado trófico del ambiente bentónico (Camilloni & Nagy et al, 2002aNagy et al, , 2008Nagy et al, , 2013García-Rodríguez et al, 2014;Pérez et al, 2016;Brugnoli et al, 2018).…”
Section: Introductionunclassified
See 1 more Smart Citation